KNOWLEDGE OF BASIC LIFE SUPPORT (BLS) in FIRST YEAR MEDICAL STUDENTS FACULTY of MEDICINE UDAYANA UNIVERSITY - Pramadyanti, Kadek Dinda; Suranadi, I Wayan; Sucandra, I Made Agus Kresna (E-Jurnal Medika Udayana; Vol 8 No 4 (2019): Vol 8 No 4 (2019): Vol 8 No 4 (2019): E-Jurnal Medika Udayana, 2019)
Basic life support is a skill in early relief measures to maintain the airway, support breathing and circulation to promote emergency oxygenation during resuscitation. These skills must be mastered to reduce the adverse effects of cardiac arrest. The purpose of this study is to determine the level of knowledge of students at the faculty of medicine Udayana University against BLS. This study is a cross sectional descriptive study conducted at the Faculty of Medicine Udayana University. The number of samples of this study is 170 from all first year course students. The study programs at Udayana University's medical faculty include medicine education programs, nursing, psychology, dentistry, physiotherapy, and public health sciences. Characteristics of data obtained by sex category dominated by male is 49 people (28.9%), by educational background dominated by medicine programs as 65 people (38.2%), and the result in each study program, the result of knowledge level on BLS is not good, while the level of knowledge is medicine education is a study program that has more knowledge from other study program that is 4 people (6,2%), nursing 2 person (8.7%) and psychology of 1 person (5.0%). Others have less knowledge. This indicates that the study program influences the level of knowledge about the BLS and from respondents who have never received and received material before have insufficient knowledge. Keywords : knowledge, BLS, BLS questionnaire, cardiac arrest